2017
DOI: 10.1101/170944
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human placental syncytiotrophoblasts restrictToxoplasma gondiivertical transmission at two distinct stages and induce CCL22 in response to infection

Abstract: 52Toxoplasma gondii is a major source of congenital disease worldwide, but the cellular and 53 molecular factors associated with its vertical transmission are largely unknown. In humans, the 54 placenta forms the key interface between the maternal and fetal compartments and forms the 55 primary barrier that restricts the hematogenous spread of microorganisms. Here, we utilized 56 primary human trophoblast (PHT) cells isolated from full-term placentas and human mid-gestation 57 chorionic villous explants to det… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
0
0
1
Order By: Relevance
“…In vitro infections showed that trophoblasts are the niche for parasite proliferation, whereas caruncular cells seem to restrict the infection, acting as a barrier to parasite transmission [10]. Parallel results in human placentas infected with Toxoplasma gondii have also been observed [35]. In the present study, immunohistochemical labelling revealed an increase in the immune cell populations associated with the maternal compartment of the placentome.…”
Section: Discussionsupporting
confidence: 81%
“…In vitro infections showed that trophoblasts are the niche for parasite proliferation, whereas caruncular cells seem to restrict the infection, acting as a barrier to parasite transmission [10]. Parallel results in human placentas infected with Toxoplasma gondii have also been observed [35]. In the present study, immunohistochemical labelling revealed an increase in the immune cell populations associated with the maternal compartment of the placentome.…”
Section: Discussionsupporting
confidence: 81%
“…Quando a infecção por T. gondii acomete embriões ou fetos, esta é conhecida como toxoplasmose congênita, e são relatados cerca de 200.000 casos no mundo a cada ano (ANDER et al, 2018). Nesse tipo de infecção ocorre a transmissão vertical da toxoplasmose quando a mulher adquire a infecção durante a gestação e encontra-se na fase aguda desta infecção (REMINGTON et al, 2001;KODJIKIAN, 2010), ou pode ser ocasionada quando a infecção na gestante ocorre antes da concepção (VOGEL et al, 1996;CHEMLA et al, 2002, BARBOSA et al, 2008CHAUDHRY et al, 2014).…”
Section: Cepas De T Gondiiunclassified